Current prospects and future challenges for nasal vaccine delivery - Helmy Yusuf; Vicky Kett (Taylor & Francis Group, 2017)
Nasal delivery offers many benefits over traditional approaches to vaccine administration. These include ease of administration without needles that reduces issues associated with needlestick injuries and disposal. Additionally, this route offers easy access to a key part of the immune system that can stimulate other mucosal sites throughout the body. Increased acceptance of nasal vaccine products in both adults and children has led to a burgeoning pipeline of nasal delivery technology. Key challenges and opportunities for the future will include translating in vivo data to clinical outcomes. Particular focus should be brought to designing delivery strategies that take into account the broad range of diseases, populations and healthcare delivery settings that stand to benefit from this unique mucosal route.